DNA Barcoding of Tenualosa toli from Estuarine Waters of Sambas and Mempawah, West Kalimantan, Indonesia - Rizal Akbar Hutagalung; Yudha Perdana Putra; Sadri; Syarif Iwan Taruna Alkadrie; Andrian Saputra; Enjang Hernandi Hidayat; Moh Rezha Sabda Firdaus; Sj Djunaidi; Yuda Saniswan; Eko Rahmanza Putra (Department of Aquaculture, 2026)
Tenualosa toli is an economically important estuarine fish in West Kalimantan; however, molecular reference data for accurate species identification remain limited. This study applied a DNA barcoding approach based on the mitochondrial cytochrome c oxidase subunit I (COI) gene to identify specimens collected from two estuaries, Mempawah and Sambas. Four samples were successfully amplified, yielding COI fragments of approximately 650–700 bp with consistent sequence lengths (682–686 bp) and no insertions, deletions, or stop codons. BLAST analysis showed high similarity to reference T. toli sequences (99.84–100%), confirming species identity. Sequence comparison revealed very limited nucleotide variation, with three samples being identical and one sample exhibiting 1–2 synonymous substitutions (<0.3%). Phylogenetic reconstruction using the neighbour-joining method grouped all samples within a single T. toli clade and clearly separated them from other Tenualosa species used as references. Given the limited sample size and the use of a single mitochondrial marker, these findings should be interpreted strictly as species-level confirmation and as an initial molecular reference rather than as evidence of population structure. The results highlight the utility of DNA barcoding for species verification and provide baseline molecular data to support future genetic studies and fisheries monitoring of T. toli in West Kalimantan.